IMPACT OF FEEDING PRACTICE ON DIVERSITY PATTERN OF THE GUT MICROBIOME IN INFANTS - Durrani, Mehwish; Nazli, Rubina; Fatima, Sadia; Bakr, Muhammad Abu (Journal of Ayub Medical College Abbottabad, 2020)
Background: The microbiome which is developed at the time of infancy remains predominant and influences the health in childhood and then throughout life through moderating different gut metabolic activities This study was designed to look for the impact of feeding practices on the diversity of gut microbiota in infants in a Pakistani cohort. Methods: A cross sectional study was carried out in 46 healthy infants [23breast-fed (BF) and 23 formula-fed (FF)], aged 0-4 months, enrolled from different centers and localities in Peshawar. Infants were screened to exclude any pathological or physiological condition that can vary the gut microbial flora such as gut surgeries and the use of antibiotics. Their stool samples were collected. DNA was extracted and subjected to next generation sequencing. Results: The results revealed that phylum Firmicutes was dominant in formula-fed infants (FF=25.4±22.7, BF=4.58±5.21), p=0.001. Similarly, Bacilli, Streptococcaceae, and Streptococcus were significantly higher in formula-fed infants. On the other hand, Selenomonadales and Streptococcus_salivarius were significantly higher in breast-fed infants with a p-value of 0.037 and 0.029 respectively when compared with formula fed infants. Conclusion: The primary colonizer of the infant’s gut is phylum Firmicutes, followed by Bacilli, Streptococcaceae, and Streptococcus in formula-fed infants and Selenomonadales and Streptococcus_salivarius in breast-fed infants. Keywords: Gut microbiota; breast-fed infants; formula-fed infants; next generation sequencing